2022
DOI: 10.1016/j.neurobiolaging.2021.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Building memories on prior knowledge: behavioral and fMRI evidence of impairment in early Alzheimer's disease

Abstract: Impaired memory is a hallmark of prodromal Alzheimer's disease (AD). Prior knowledge associated with the memoranda improves memory in healthy individuals. However, little is known about its effect in early AD. We used functional MRI to investigate whether prior knowledge enhances memory encoding in early AD, and whether the nature of this prior knowledge matters. 17 patients with early AD and 19 controls underwent a task-based fMRI experiment where they learned face-scene associations. Famous faces carried pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…The experiment failed to demonstrate novelty-related boosting effect; recognition memory performance was better for well-known than novel stimuli. This suggests that prior knowledge is a more powerful facilitator of encoding in episodic memory than novelty, at least in this kind of paradigm (Bird et al, 2011;Jonin et al, 2022). Moreover, aMCI patients had worse recognition performance than controls for familiar items, but not for novel items.…”
Section: Introductionmentioning
confidence: 91%
“…The experiment failed to demonstrate novelty-related boosting effect; recognition memory performance was better for well-known than novel stimuli. This suggests that prior knowledge is a more powerful facilitator of encoding in episodic memory than novelty, at least in this kind of paradigm (Bird et al, 2011;Jonin et al, 2022). Moreover, aMCI patients had worse recognition performance than controls for familiar items, but not for novel items.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, some studies have shown reduced posterior cingulate gyrus/precuneus activation and hyperactivation in frontal regions, including the precentral gyrus, in MCI patients in comparison to CN individuals during memory tasks (Hampstead et al ., 2011 ; Jin et al ., 2012 ; Terry et al ., 2015 ). In AD, MTL hypoactivation, reduced posterior cingulate gyrus/praecuneus deactivation and frontal hyperactivation are approximately consistent findings during memory tasks (Canário et al ., 2022 ; Jonin et al ., 2022 ; Parra et al ., 2013 ; Petrella et al ., 2007 ; Pihlajamäki and Sperling, 2009 ; Yetkin et al ., 2006 ).…”
Section: Mrimentioning
confidence: 99%